OP18 IDENTIFICATION AND CHARACTERISATION OF MICRORNAS INVOLVED IN GLIOBLASTOMA CELL PROLIFERATION AND SURVIVAL - Boissinot, M. (Oxford University Press, 2014)
INTRODUCTION: There is a pressing need for new therapeutic approaches for the treatment of glioblastoma (GBM). MicroRNAs(miRs)are single-stranded non-coding RNAs, 22-24nt in length, that function by reducing translation or causing degradation of target mRNAs. MiRs have been shown to play roles in multiple hallmark characteristics of GBM,suggesting that miRs and their associated pathways may be of therapeutic importance. METHOD: The miRIDIAN mimic library (Dharmacon) that encompasses all human miRs annotated in miRBase v16.0 was used with a high-throughput imaging platform (Operetta) to identify miRs with potent effects on GBM cell proliferation and survival. Screens were performed in duplicate on U251 (adult) and KNS42 (paediatric) GBM cell lines. Cell number was assessed 72h post-transfection and expressed as z-scores of the nuclei count. MiRs were considered significant candidates if their mean z-score was below zero, indicating a decrease in cell number, and if it differed from that of the negative control by at least two standard deviations.Validation included RTqPCR, imaging and flow cytometry based assays. RESULTS: For each cell line, the functional screen resulted in approximately 100 candidates, of which 70% were in both cell lines. Seven miRs were validated in a panel of 4 adult and 2 paediatric GBM cell lines.Mir-X was identified as the most potent, robust candidate involved in GBM cell death across all cell lines. This miR consistently caused a G2M cell cycle arrest followed by apoptosis. CONCLUSION: We have identified a novel potent pro-apoptotic miR in GBM that may be relevant in therapy. Work is ongoing to characterise the targets and mechanisms responsible for this effect and test for efficacy in vivo.